One Size Fits All? Disentangling the Effects of Tobacco Taxes, Laws, and Control Spending on Adult Subgroups in the United States. Issue 1 (January 2019) - Yu, Hao; Engberg, John; Scharf, Deborah
Background : To determine the relative impact of each of the 3 state-level tobacco control policies (cigarette taxation, tobacco control spending, and smoke-free air [SFA] laws) on adult smoking rate overall and separately for adult subgroups in the United States. Methods : A difference-in-differences analysis was conducted with generalized propensity scores. State-level policies were merged with the individual-level Behavioral Risk Factor Surveillance System in 1995–2009. Results : State cigarette taxation was the only policy that significantly impacted smoking among the general adult population, with a 1-standard deviation increase in taxes (i.e., 0.68 in constant 2014 dollars) lowering the adult smoking rate by about a quarter of a percentage point. The taxation impact was consistent, regardless of the presence of, or interactions with, other policies. Taxation was also the only policy that significantly reduced smoking for some adult subgroups, including females, non-Hispanic whites, adults aged 51 or older, and adults with more than a high school education. However, other adult subgroups responded to the other 2 types of policies, either by mediating the taxation effect or by reducing smoking independently. Specifically, tobacco control spending reduced smoking among young adults (ages 18–25 years) and Hispanics. SFA laws affected smoking among men, young adults, non-Hispanic blacks, and Hispanics. Conclusions : State cigarette taxation is the single most important policy for reducing smoking among the general adult population. However, adult subgroups' reactions to taxes are diverse and mediated by tobacco control spending and SFA laws.